The Use of Learning Aids for Dyscalculia: Systematic Literature Review - Husna Fatwana; Dadan Dasari; Dadang Juandi (AL-ISHLAH: Jurnal Pendidikan, 2023)
The aim of this research is to examine appropriate learning aids for dyscalculia children. Systematic literature review became the method in this study. This article reviews 13 articles involving more than 4939 subjects and respondents. We reviewed articles published from 2010 to 2021 from the Sage, SpringerLink, TaylorFrancis, and Wiley Online Library databases. All articles were classified by year, research approach, research objectives and strategies offered for dyscalculia children. The selection of articles found the use of manual tools and the use of technological aids. The results of the review analysis showed that learning with the help of technology had a greater impact on the learning outcomes of dyscalculia students.